Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Question Suppose $u$ and $v$ are in $L^1(0,T; X)$ where $X$ is Banach. Suppose v = u' in the distributional sense. I want to show that, for $w \in X^*$, that $$\frac{d}{dt}\langle w, u \rangle = \langle w, v \rangle$$ implies $$\langle w, \int_0^T \phi' u + \int_0^T \phi v\rangle = 0$$ for all $\phi \in C_c^\infty(0,T)$.

Attempt I can get no further than this (please check if I am right): By definition, we have $$\int_0^T \langle w, u \rangle \phi' = -\int_0^T \langle w, v \rangle \phi$$ hence $$\int_0^T \langle w, u \rangle \phi' + \langle w, v \rangle \phi \;dt= 0$$ which is $$\int_0^T w(u) \phi' + w(v)\phi \;dt= 0$$ and by linearity $$\int_0^T w(\phi' u) + w(\phi v) \;dt= 0$$ so $$\int_0^T w(\phi' u) + \int_0^T w(\phi v) = \int_0^T \langle w, \phi' u\rangle + \int_0^T \langle w, \phi v\rangle $$ Where to go from here? How can I put the integral inside the functional? Also I am not sure if I am using the linearity property of functionals correctly, since I am assuming that $\phi$ doesn't depend on $X$. Thanks

share|cite|improve this question
up vote 1 down vote accepted

The only result needed now it that if $L\in X^*$ and $f\in L^1(0,T;X)$, then $$\int_{(0,t)}L(f(t))dt=L\left(\int_{(0,t)}f(t)dt\right).$$ To see that, we use $s_n(t)$ for $t\in (0,T)$, a simple function such that $s_n(t)\to f(t)$ for all $t$ and in $L^1$. So we just have to deal with the case $f$ simple, and in this case it follows from linearity of the integral.

share|cite|improve this answer
Thanks. If $f$ is simple, it means $f(t) = \sum_{i}a_i(t)\mathbb{1}_{A_i(t)}(x),$ right? If so, I can't get your claim to work. – soup Oct 28 '12 at 12:58

For the strong distributional derivative one has by linearity of functionals: $$\int(u\varphi'+v\varphi)\mathrm{d}\mu=0\implies\langle w^*,\int(u\varphi'+v\varphi)\mathrm{d}\mu\rangle=\langle w^*,0\rangle=0$$ For the weak distributional derivative one has by a special property of integral: $$\langle w^*,\int(u\varphi'+v\varphi)\mathrm{d}\mu\rangle=\int\langle w^*,u\varphi'+v\varphi\rangle\mathrm{d}\mu=0\implies\int(u\varphi'+v\varphi)\mathrm{d}\mu=0$$ (Note that the dual of Banach spaces separates points.)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.